Pelatihan Microsoft Office Word bagi Siswa Kelas VI SD Negeri 1 Desa Kecomberan Kecamatan Talun Kabupaten Cirebon - Aris Riyanto; Marlianita, Rini (Darma Abdi Karya, 2023)
The Microsoft Office application plays a crucial role in today's digital era, utilized by various groups ranging from primary school children to university students and professionals. Its usage is increasingly popular across different sectors, including offices and the education sector. As a result, training activities are carried out within the context of community service through the Thematic Community Service Program (KKN Tematik) of Politeknik LP3I Cirebon Campus. The purpose of this training is to enhance the knowledge and understanding of primary school students, particularly in the use of Microsoft Word and Microsoft Excel. This training takes place at SD Negeri 1 Kecomberan. The outcomes of this training demonstrate that participants are enthusiastic and capable of answering post-test questions related to basic Microsoft Word knowledge effectively. The method employed involves providing guidance to students to directly practice the conveyed material. In conclusion, this training provides significant benefits to primary school students in enhancing their knowledge of Microsoft Office applications, specifically Microsoft Word.